PENYEBUTAN DAN PENGGUNAAN HADI>>>N: Sudut Pandang Kajian Hadi>th Warga NU Desa Gadingmangu Kecamatan Perak Kabupaten Jombang - Khamim Khamim (IAIN Ponorogo, 2019)
Abstract: This article scrutinize the habits of '(Nahdiyyi>n) people in Gadingmangu Village, Perak District, Jombang Regency, related to the meaning of hadi>th. Besides the NU community, LDII people who have more or less different points of view in the study of hadith in this area. Consequesntly, Nahd iyyi> n community in this region has considerable responsibility in delivering hadith studies to their next generation. This studyindicsted that in the way to declare hadith, the people of Nahdiyyi>n are accustomed to mention the first narrator / final sanad, the narrator of the hadi>th (Rasu> l Alla> h), and matn of hadith in Arabic speaking or even only with translations from matn. They frequently refer to the statement